2013
DOI: 10.1162/rest_a_00304
|View full text |Cite
|
Sign up to set email alerts
|

Competition Policy and Productivity Growth: An Empirical Assessment

Abstract: Abstract-This paper estimates the impact of competition policy on total factor productivity growth for 22 industries in twelve OECD countries over 1995 to 2005. We find a positive and significant effect of competition policy as measured by created indexes. We provide results based on instrumental variables estimators and heterogeneous effects to support the causal nature of the established link. The effect is particularly strong for specific aspects of competition policy related to its institutional setup and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(50 citation statements)
references
References 62 publications
3
39
0
1
Order By: Relevance
“…It might also be that by assuming constant returns to scale for the computation of TFP we induce a bias in the coefficient of the mark-up in equation (1). As shown in Griffith et al (2007) and Buccirossi et al (2013), markups and returns to scale are positively correlated. Hence, the difference between constant returns to scale TFP and actual TFP, i.e., the measurement bias in TFP, is positively correlated with the mark-up, which may bias upwards the estimated coefficient b 1 in equation (1).…”
Section: Data Sourcesmentioning
confidence: 81%
“…It might also be that by assuming constant returns to scale for the computation of TFP we induce a bias in the coefficient of the mark-up in equation (1). As shown in Griffith et al (2007) and Buccirossi et al (2013), markups and returns to scale are positively correlated. Hence, the difference between constant returns to scale TFP and actual TFP, i.e., the measurement bias in TFP, is positively correlated with the mark-up, which may bias upwards the estimated coefficient b 1 in equation (1).…”
Section: Data Sourcesmentioning
confidence: 81%
“…on average 1.04 million € per year, revealed that the direct benefits to consumers brought by the Competition Council exceeded its annual budget by 12.6 times or by almost 75 times (if deterrence effect is included). statements about the absent or low deterrent effect of antitrust policy are opposed by the latest theoretical works ) and empirical research (Buccirossi et al 2013;Allain et al 2011;Clarke and Evenett 2003;Owen 2003), providing evidence that the development of antitrust policy enforcement strengthens market competition and that strongly enforced antitrust law has a deterrent effect; that is, it is expected to decrease the rate of overcharge and prevent illegal price-fixing behaviour in the future. As stressed by Buccirossi et al (2013), by deterring anti-competitive practices competition policy makes markets work effectively and fosters efficiency, and that good competition policy has a strong impact on total factor productivity 5 growth.…”
Section: Cartels and Antitrust Policymentioning
confidence: 99%
“…Our results make an important contribution to the literature on economic growth, by assessing the distinct effect of independent variables on the two components of TFP growth, innovation (technical change) and imitation (efficiency change) and resolving two common economic puzzles. The first of these is the counter-intuitive and frequently obtained result of the non-significant or positive influence of anticompetitive regulation variables on productivity growth, as is the case in some specific versions of the models of Aghion et al (2009, Nicoletti and Scarpetta (2003), Inklaar et al (2008) or Buccirossi et al (2009). The second puzzle refers to the non-significant or negative influence of research intensity on productivity growth that is obtained in some specifications such as in the work of Saxena et al (2008), Ulku (2007b), Islam (2009), Madsen (2008 or Barcenilla et al (2011).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%